Studi Komparatif Ayat-Ayat Kejujuran Dalam Al-Qur'an Dan Implementasinya Pada Pembentukan Karakter Muslim - Novianti, Cindi; Sujiono, Duta Bahagia Rizki; Damanik, Muhammad Zein (STAI Tebing Tinggi Deli, 2024)
This study aims to comparatively examine the verses about honesty in the Qur'an and explore its implementation in the character building of a Muslim. Honesty is one of the fundamental values in Islam that becomes the main foundation in forming a person with integrity. The method used in this research is thematic and comparative analysis of the Qur'anic verses related to honesty. The data is collected through literature review and supported by the interpretation of classical and contemporary tafsir scholars. The results show that the concept of honesty in the Qur'an not only includes honesty in words, but also in deeds, intentions, and commitment to trust. The implementation of the value of honesty has proven to play an important role in shaping the character of Muslims who are responsible, trustworthy, and consistent in living their daily lives. This research makes a significant contribution to the development of a character education model based on Qur'anic values that can be applied in various contexts, including formal education, family, and society